Lettera del card. Sebastiano Baggio a mons. Álvaro del Portillo del 17 gennaio 1983, sulle prelature personali / A letter from Cardinal Sebastiano Baggio to Monsignor Álvaro del Portillo dated 17th January 1983, about Personal Prelatures - José Luis Illanes (Studia et Documenta)
Publication of a letter from Cardinal Sebastiano Baggio, Prefect of the Congregation for Bishops, dated 17 January 1983, addressed to Msgr Álvaro del Portillo, the Prelate of Opus Dei. In the letter, the Prefect informs the Prelate that he had been received by Pope John Paul II in an audience on 8 January 1983. He also states that on this occasion, the Pope had clarified de meaning and the scope of the change of the positioning of the canons concerning personal prelatures in de Code of Canon Law of 1983.